Health Care Quality in CKD Subjects: A Cross-Sectional In-Hospital Evaluation - L. Rzayeva; I. Matyukhin; O. Ritter; S. Patschan; D. Patschan (International Journal of Nephrology)
Background and Aim. Chronic kidney disease (CKD) is an emerging problem in both clinical and ambulatory medicine. Much effort in terms of managing CKD must be put into the control of so-called progression factors. In the current investigation, we evaluated the CKD-associated health care quality in all in-hospital subjects that were treated in a newly founded university hospital for a period of 1 year. Methods. The study was performed in a retrospective and observational manner. All adult (age 18 years or older) in-hospital subjects treated from January until December 2019 were included. CKD was diagnosed according to the KDIGO 2012 CKD Guideline. The following variables were assessed: CKD stage, quantification/analysis (yes/no) of blood pressure, proteinuria, serum phosphate, serum 25-OH-D3, ferritin and transferrin saturation, and blood gas analysis. In addition, recommendations of the following medicines were analyzed (given/not given): ACE inhibitor or sartan, phosphate binder, vitamin D3 (activated or native), iron, erythropoietin, and bicarbonate. It was also evaluated whether discharge letters contained CKD-related diagnoses or not. Results. In total, 581 individuals were included in the study. The majority of aspects related to the monitoring and therapeutic management of CKD were either considered in only a small proportion of affected individuals (e.g., quantification of PTH − 5.5%/25-OH-D3 − 6%/transferrin saturation − 13.6%) or avoided nearly at all (e.g., recommendation of erythropoietin—1%, documentation of CKD-MBD diagnosis—0.3%). A reasonable quality of care was identified concerning the blood pressure monitoring (performed in 100%) and blood gas analysis (55% of the patients received analysis). Serum phosphate was measured in 12.9%, particularly in subjects at higher CKD stages. Conclusions. The current investigation revealed poor quality of care in CKD patients treated at the Brandenburg University Hospital over the period of one year. Quality improvement must be achieved, most likely via a standardized educational program for physicians and a directer access to CKD management guidelines.